2017
DOI: 10.1089/jwh.2015.5639
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Initial Local Treatment of Older Women with Early-Stage Breast Cancer: A Population-Based Study

Abstract: Over half of older women with ESBC initially receive BCS+RT. The likelihood for mastectomy and BCS only increases with age, comorbidity, and vulnerable socio-demographic characteristics. Findings demonstrate continued treatment disparities among certain vulnerable populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Despite flexibility in treatment guidelines, treatment disparities reported by previous studies raise concern that older women are undertreated more frequently than warranted. Recent studies have reported that among women aged ≥65 years, 21% to 29% did not receive RT following BCS for early-stage breast cancer regardless of their ER status, 4,15 67% with lymph node–positive disease did not receive chemotherapy, 9 50% did not receive trastuzumab, 16 and 17% to 40% did not receive AET when indicated. 5 Moreover, age and comorbidity have been found to be the strongest predictors of treatment, irrespective of clinical indications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite flexibility in treatment guidelines, treatment disparities reported by previous studies raise concern that older women are undertreated more frequently than warranted. Recent studies have reported that among women aged ≥65 years, 21% to 29% did not receive RT following BCS for early-stage breast cancer regardless of their ER status, 4,15 67% with lymph node–positive disease did not receive chemotherapy, 9 50% did not receive trastuzumab, 16 and 17% to 40% did not receive AET when indicated. 5 Moreover, age and comorbidity have been found to be the strongest predictors of treatment, irrespective of clinical indications.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive analyses of local-regional treatment patterns (mastectomy vs. lumpectomy alone vs. lumpectomy+radiation) in elderly women with early-stage breast cancer are few. Lemasters et al has performed the most detailed analysis using SEER-Medicare data from 2003 to 2009 (16). Comparisons with our study are limited as Lemasters et al included women with higher stage breast cancer (stage II), ER- disease, and younger women aged 66–69 years old.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that patients who received Japanese standard high tangent field radiotherapy after surgery had better DFS and OS than those in the nonirradiated group. Radiation therapy is sometimes omitted owing to older age or comorbidities . Since this study included patients with various characteristics and age ranges, propensity‐score–matched analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…When the resection margin was close to the cancer lesion after breast‐conserving surgery, 10.0 Gy was added as a boost for all patients . For some of elderly patients aged over 70 years, hypofractionated radiation therapy (42.4 Gy in 16 fractions) with or without boost addition (10.6 Gy in 4 fractions) and radiation omission were options if she or he could receive endocrine therapy for luminal A‐like, stage I disease …”
Section: Introductionmentioning
confidence: 99%